'Something than which nothing greater can be thought' and Kant's Ens Realissimum. (11th July 2021) - Jackson, Morgan Keith
Abstract: In this paper, I explore Kant's much‐studied critique of the ontological argument, seeking to place Immanuel Kant and Anselm of Canterbury more directly in contact with one another; I do this in two ways. First, I discuss the historical reception of the ontological argument in Kant's eighteenth century context. Second, I move the discussion away from the first Critique, and look towards Kant's Pre‐critical discussion of the ontological argument in The Only Possible Argument, where he initially sets out his primary objection. By shifting the focus towards these areas of Kant's thought, I aim to achieve three interrelated goals. First, I show that Kant had a limited knowledge of the history and origins of the ontological argument, which was transmitted to him through Leibniz, Wolff, and Baumgarten, who put a Cartesian spin on it. Second, I provide textual evidence which shows that Kant's objection does not succeed against Anselm's argument. Third, I elucidate that Kant's identification of God as the ens realissimum is compatible with Anselm's identification of God as 'something than which nothing greater can be thought'.